High-Q enstatite microwave/terahertz dielectric ceramics modulated by phase transition and lattice distortion - Yutian Lu; Weijia Guo; Chongyang Zhang; Hui Zhang; Zhenxing Yue (Journal of Advanced Ceramics)
The rapid development of fifth-/sixth-generation telecommunication technologies has increased the demand for silicate ceramic materials with low permittivity and low dielectric loss. However, few silicate ceramics with ultrahigh Q×f values (≥ 200,000 GHz) have been developed to date. In this study, a slight substitution of Ge4+ ions in MgSi1−xGexO3 (MSGx, x = 0 to 0.6) ceramics caused a phase transition from clinoenstatite (x = 0) to orthoenstatite (x = 0.2), and the Q×f value increased from 70,600 GHz to 148,800 GHz. Following the phase transition, the cations change from a “compressed” state to a “rattle” state, and the lattice distortion continues to rise with x, resulting in the optimal microwave dielectric properties (εr = 7.21, Q×f  = 259,300 GHz) of the MgSi0.5Ge0.5O3 ceramics. Significant discrepancies in the dielectric properties are found in the microwave and terahertz bands. There is an anomalous increase in εr and a decrease in the Q×f value in the terahertz band, which is due to the change in polar phonon modes revealed by the terahertz time-domain spectra. Consequently, MgSi0.7Ge0.3O3 ceramics display superior dielectric properties, with εr = 7.02, Q×f  = 191,300 GHz in the terahertz band. These novel materials have the potential to serve as promising dielectric materials for future microwave or terahertz mobile communication systems.